2022
DOI: 10.3390/ijms23105479
|View full text |Cite
|
Sign up to set email alerts
|

CD133-Functionalized Gold Nanoparticles as a Carrier Platform for Telaglenastat (CB-839) against Tumor Stem Cells

Abstract: The failure of a long-lasting curative therapeutic benefit of currently applied chemotherapies against malignant cancers is suggested to be caused by the ineffectiveness of such interventions on cancer stem cells (CSCs). CD133/AC133 is a cell surface protein previously shown to have potential to identify CSCs in various tumors, including brain tumors. Moreover, an increase in the rate of cellular metabolism of glutamine and glucose are contributors to the fast cellular proliferation of some high-grade malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Recently, a 15-nucleotide base-pair aptamer targeting CD133 was loaded on Au-PEG NPs to deliver the drug Telaglenastat (CB-839). Au-PEG-CD133-CB-839 particles exerted a strong decrease in the GBM cell lines’ survival compared to controls [ 87 ]. Affinito et al described an RNA aptamer that selectively targets the Ephrin A-2 on the cell surface of GCSs, inhibiting tumor stemness and migration [ 86 ].…”
Section: Relevant Cargoes For Brain Cscsmentioning
confidence: 99%
“…Recently, a 15-nucleotide base-pair aptamer targeting CD133 was loaded on Au-PEG NPs to deliver the drug Telaglenastat (CB-839). Au-PEG-CD133-CB-839 particles exerted a strong decrease in the GBM cell lines’ survival compared to controls [ 87 ]. Affinito et al described an RNA aptamer that selectively targets the Ephrin A-2 on the cell surface of GCSs, inhibiting tumor stemness and migration [ 86 ].…”
Section: Relevant Cargoes For Brain Cscsmentioning
confidence: 99%
“…ZEB1 as a key element of EMT promotion has been extensively studied in different brain tumors, particularly GBM. GBM is the most aggressive malignant primary brain tumor in which a variety of therapeutic strategies have failed to demonstrate efficacy [ 155 ]. Several investigations have reported that the ZEB1 pathway contributes to GBM initiation and progression, invasion, radioresistance, and chemoresistance.…”
Section: Zeb1 Effects In Cns Tumorsmentioning
confidence: 99%
“…Further investigation of the mechanism was performed by another study, which showed that the sensitivity to CB-839 in GSCs was not due to the contribution of glutaminolysis to the TCA cycle; rather, the sensitivity was brought on by reduced intracellular glutamate, which led to the amino acid deprivation response (AADR) [ 149 ]. Continuing this line of research, a modification of the CB-839 delivery route was developed by loading the drug into PEGylated gold nanoparticles with conjugated CD133 aptamers (Au-PEG-CD133-CB-839) [ 150 ]. The conjugation of CD133, a surface marker recognized on CSCs, was intended to improve the targeting of this drug to CSCs.…”
Section: Glutaminolysis-specific Intervention For Cscsmentioning
confidence: 99%
“…Making use of the small size and high biocompatibility of gold nanoparticles, this design contributes to improved permeability of the BBB and penetration of the tumor. A preliminary in vitro study demonstrated that Au-PEG-CD133-CB-839 significantly decreased the viability of CD133-positive cancer cells in comparison with treatment with CB-839, in which a dose-dependent effect was seen [ 150 ]. This highlighted a feasible strategy for the targeting of CSCs, while further studies in cells that are not restricted to CD133-positive populations are warranted to validate its effect.…”
Section: Glutaminolysis-specific Intervention For Cscsmentioning
confidence: 99%